Correlation between Phase Behavior and Interfacial Tension for Mixtures of Amphoteric and Nonionic Surfactant with Waxy Oil - Rani Kurnia; Deana Wahyuningrum; Doddy Abdassah; Taufan Marhaendrajana (Journal of Engineering and Technological Sciences, 2021)
Phase behavior tests in the surfactant screening process for EOR applications remain one of the relatively convenient ways to design an optimum surfactant formulation. However, phase behavior studies are unable to provide quantitative data for interfacial tension, which is one of the parameters that must be considered when selecting surfactants for EOR. Several studies related to the prediction of interfacial tension through phase behavior testing have been carried out. In this paper, the Huh correlation was used to estimate the interfacial tension value based on phase behavior tests. It was found that the current form of the Huh correlation may be applied for the below-to-optimum salinity condition. Furthermore, the constants of the equation vary depending on the surfactant type and mixtures.